Temporal response of soil organic carbon after grassland‐related land‐use change. (17th June 2018) - Li, Wei; Ciais, Philippe; Guenet, Bertrand; Peng, Shushi; Chang, Jinfeng; Chaplot, Vincent; Khudyaev, Sergey; Peregon, Anna; Piao, Shilong; Wang, Yilong; Yue, Chao
Abstract: The net flux of CO2 exchanged with the atmosphere following grassland‐related land‐use change (LUC) depends on the subsequent temporal dynamics of soil organic carbon (SOC). Yet, the magnitude and timing of these dynamics are still unclear. We compiled a global data set of 836 paired‐sites to quantify temporal SOC changes after grassland‐related LUC. In order to discriminate between SOC losses from the initial ecosystem and gains from the secondary one, the post‐LUC time series of SOC data was combined with satellite‐based net primary production observations as a proxy of carbon input to the soil. Globally, land conversion from either cropland or forest into grassland leads to SOC accumulation; the reverse shows net SOC loss. The SOC response curves vary between different regions. Conversion of cropland to managed grassland results in more SOC accumulation than natural grassland recovery from abandoned cropland. We did not consider the biophysical variables (e.g., climate conditions and soil properties) when fitting the SOC turnover rate into the observation data but analyzed the relationships between the fitted turnover rate and these variables. The SOC turnover rate is significantly correlated with temperature and precipitation ( p < 0.05), but not with the clay fraction of soils ( p > 0.05). Comparing our results with predictions from bookkeeping models, we found that bookkeeping models overestimate by 56% of the long‐term (100 years horizon) cumulative SOC emissions for grassland‐related LUC types in tropical and temperate regions since 2000. We also tested the spatial representativeness of our data set and calculated SOC response curves using the representative subset of sites in each region. Our study provides new insight into the impact grassland‐related LUC on the global carbon budget and sheds light on the potential of grassland conservation for climate mitigation. Abstract : Soil organic carbon (SOC) change after land‐use change (LUC) is critical to estimate historical LUC emissions and evaluate future land‐based climate mitigations. Here, we compiled a global data set to characterize the temporal dynamics of SOC changes after LUC disturbances for all climate zones and most soil types. We separated between SOC losses from the initial ecosystem and gains from the secondary one by combining satellite‐based NPP observations as a proxy of SOC input. Our results show that the models used for estimating LUC carbon emissions from grasslands overestimate long‐term cumulative SOC losses.